Penentuan Jumlah Loket Pembayaran Telepon Yang Optimal Dengan Model Simulasi Di Bank X Surabaya - Soejanto, Irwan (JURNAL TEKMAPRO, 2007)
ABSTRACT Every month telephone users pay their telephone bill in TELKOM outlets or banks. Nowadays, Bank X Surabaya has 2 (two) telephone bill payment windows with long queue. In this case, the computer simulation model is used to find an effective queue system to anticipate customersâ dissatisfaction. Using Software Arena and Simul8, the model system is simulated into software to describe how the system works. The real system simulationÂ shows that the average ofÂ utilization level of 2 telephone bill payment windows areÂ 94% and after tryingÂ 3 telephone bill payment windows in trial and error simulation, it shows that the average ofÂ utilization levelÂ reduce to 36%, so that customersâ satisfaction increase. Keywords: simulation, queue, amount of telephone bill payment window